2021
DOI: 10.1002/cssc.202100141
|View full text |Cite
|
Sign up to set email alerts
|

Flame‐Retardant, Highly Conductive, and Low‐Temperature‐Resistant Organic Gel Electrolyte for High‐Performance All‐Solid Supercapacitors

Abstract: Traditional liquid electrolytes are volatile, flammable, and easy to leak, which makes the energy storage device easy to burn and explode in the case of overcharge and short circuit. Here, by utilizing the active PÀ H bond of a flame retardant (DOPO) to graft onto the polymer chain, flame-retardant organic gel electrolytes were fabricated to address these issues. The gel electrolyte had good ionic conductivity of 4 mS cm À 1 at 20°C and good flame retardant ability. By changing the molar ratio of the monomers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…As an important part of energy storage devices, the freezing resistance of electrolytes directly affects the low-temperature performance of energy storage devices. Although a large number of studies are reported DOI: 10.1002/advs.202201679 on non-aqueous electrolytes with low melting point, [1][2][3][4][5] such as liquefied gas, [2] fluorinated solvent, [3] and ethyl acetate, [4] these non-aqueous electrolytes are usually costly, leaky, flammable and toxic, restricting their applications. In contrast, water-based electrolytes perform well in terms of low cost, non-flammability and non-toxicity, etc.…”
Section: Introductionmentioning
confidence: 99%
“…As an important part of energy storage devices, the freezing resistance of electrolytes directly affects the low-temperature performance of energy storage devices. Although a large number of studies are reported DOI: 10.1002/advs.202201679 on non-aqueous electrolytes with low melting point, [1][2][3][4][5] such as liquefied gas, [2] fluorinated solvent, [3] and ethyl acetate, [4] these non-aqueous electrolytes are usually costly, leaky, flammable and toxic, restricting their applications. In contrast, water-based electrolytes perform well in terms of low cost, non-flammability and non-toxicity, etc.…”
Section: Introductionmentioning
confidence: 99%
“…4g). 52,53 Furthermore, Fig. 4h shows that the SC devices still have a specific capacitance retention of 87% even after 3000 bending cycles, and the image of the device after 3000 cycles revealed that no appreciable mechanical cracks could be observed in the organo-hydrogel electrolyte, which indicated the excellent mechanical stability of the gel after cycling deformation.…”
Section: Resultsmentioning
confidence: 93%
“…The substitution of traditional flammable organic solvents to non-flammable ionic liquids (ILs) in GPEs (termed ionogels) could significantly increase their fire retardance. [9][10][11] The incorporation of ILs in a poly(ionic liquids) network resulted in the formation of an ionogel electrolyte with high ionic conductivity (2.5 mS cm −1 ) and desirable mechanical properties (2.5 MPa), and it also could maintain its original size even at 150 °C and hardly be ignited by a flame. 12 Compared with polymer ionogels, hydrogel electrolytes are cheaper and intrinsically enhance the flame resistance and delay the combustion of the device, but it is still difficult to achieve absolute flame resistance.…”
Section: Introductionmentioning
confidence: 99%